IMPACT OF TRUCK DRIVERS’ STRIKE ON RISK MANAGEMENT IN SUPPLY CHAINS: THE CASE OF A HOSPITAL IN THE STATE OF MINAS GERAIS: IMPACT OF TRUCK DRIVERS’ STRIKE ON RISK MANAGEMENT IN SUPPLY CHAINS: THE CASE OF A HOSPITAL IN THE STATE OF MINAS GERAIS - Barra , Geraldo Magela Jardim; Silva, Rodrigo Oliveira da; Silveira, Rebecca Impelizieri Moura da (Brazilian Journal of Production Engineering, 2020)
This article aims to demonstrate the importance of a risk management plan for supply chain management in the hospital sector. The risk mitigating actions of a hospital were analyzed during the truckers’ strike that occurred in May 2018. A single case study was used, approached with a set of evidence collection instruments, both through analysis of the reports of the institution’s manager target and document analysis. We opted for content analysis with categories established a priori and concerning the risk management literature in supply chains. The fundamental factor used by the hospital as a mitigation strategy was the quality program with a contingency plan and the hospital’s relationship with its relationship networks. The sharing of information between these organizations was essential for the hospital to maintain the quality of the services provided.